2022
DOI: 10.1177/03611981221114118
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Spatial and Temporal Dilemma Zone at Mid-Block Median Openings: A Gap Acceptance Based Approach

Abstract: A U-turn at a mid-block median opening (MBMO) is a complex maneuver. The U-turning vehicle has to find a suitable gap between two fast-moving vehicles in the approaching through traffic (ATT) stream and decide whether to accept or reject the available gap. Incorrect judgment of an available gap may lead to congestion or a collision between the U-turning vehicle and ATT. Frequently, U-turning vehicles are in a state of dilemma while deciding whether to reject or accept the available gap. Under these scenarios, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The U-turn is a complex process because the U-turning driver must judge the available gap in the opposing stream based on their perception and make a decision whether to proceed with the merging process or wait for the next available gap. The decision also varies for the same driver based on difference in traffic conditions, speed of the traffic in opposing stream, and the psychological character of the driver such as angry, happy, frustrated, and so on ( 15 ). Thus, MBMOs are considered as one of the potential hotspots for traffic congestion and conflict.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The U-turn is a complex process because the U-turning driver must judge the available gap in the opposing stream based on their perception and make a decision whether to proceed with the merging process or wait for the next available gap. The decision also varies for the same driver based on difference in traffic conditions, speed of the traffic in opposing stream, and the psychological character of the driver such as angry, happy, frustrated, and so on ( 15 ). Thus, MBMOs are considered as one of the potential hotspots for traffic congestion and conflict.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liu et al ( 12 ) carried out a study in the United States of America on a six-lane road and reported conflicting traffic volume as 2.2 times approaching traffic volume in each lane. This finding for the estimation of conflicting traffic volume is not suitable under the heterogeneous traffic conditions found in developing economies, such as India, where different types of vehicles of varying physical and dynamic characteristics (size, age of vehicle, and efficiency of vehicle), use the same road section simultaneously without any physical separation ( 14 , 15 ). Also, driver characteristics, location geometry, and design vary significantly.…”
mentioning
confidence: 98%
“…A U -turn at a midblock median opening is a complicated maneuver that causes drivers to be unsure whether to accept or reject the available gap in order to prevent a collision with opposing traffic flow. The study by Khan and Mohapatra in 2022 analyzed the dilemma zone for U-turning vehicles at a midblock median opening for different vehicle categories, and they concluded that the dilemma zone would be highly affected by the vehicle size [ 9 ].…”
Section: Related Workmentioning
confidence: 99%
“…Studies have analyzed and quantified the pedestrian dilemma zone for the uncontrolled midblock section ( 15 , 16 ). It has been noted that different types of vehicles have an impact on the length and location of the dilemma zone ( 17 ). According to these studies, the speed of the approaching vehicle, vehicle type, pedestrian type, crossing speed, and pedestrian waiting time all affect the length and location of the pedestrian dilemma zone.…”
mentioning
confidence: 99%